Hubungan Beban Kerja Terhadap Produktivitas Kerja Karyawan di PT Multiagro Sumatera Jaya (MSJ) Kecamatan Kualuh Hulu - Viona Afiqah; Utami, Tri Niswati; Aidha, Zuhrina (LPPM Hang Tuah Pekanbaru, 2024)
Conditions have the potential to influence the failure to achieve production targets at PT Multiagro Sumatra Jaya (MSJ) in Kualuh Hulu District, where a workload that is too large is assigned to employees. The workload that employees must complete is not balanced with the work time allotted for production. This research aims to determine the relationship between workload and employee work productivity at PT Multiagro Sumatra Jaya (MSJ) in Kualuh Hulu District. The research employed a quantitative research method with a cross-sectional design. It was conducted at PT Multiagro Sumatra Jaya (MSJ) in Kualuh Hulu District, with a population of 120 workers. An accidental sampling technique was used to select a sample of 61 participants who completed a questionnaire as the research instrument. The data collected were processed using SPSS to analyze univariate and bivariate Chi-square tests. Based on the results of the Chi-square test, it was found that moderate workload conditions had the largest category about medium work productivity levels, with a significant p-value of 0.036 < 0.05. This indicates a significant relationship between workload and work productivity among workers in the processing section at PT Multiagro Sumatra Jaya (MSJ). Workload emerges as the most frequently cited factor affecting every worker, with its intensity increasing as the company advances.